(untitled) (Journal of Oriental Studies, 2025)
This study examines Iran’s national strategy for Persian language dissemination through standardized testing, focusing on the AMFA, AZFA, and particularly the SAMFA proficiency examinations. Situated within the border frameworks of language policy, corpus-based testing, and assessment theory, the paper explores the development, administration, and theoretical underpinnings of these tests. SAMFA, the most internationally recognized and academically aligned test, is analyzed in detail with reference to task design, linguistic content, and CEFR compatibility. Drawing on corpus linguistics (e.g. Peykareh), communicative competence models, and applied linguistic theory, the study reveals tensions between cultural authenticity and standardization. It highlights the structural and sociolinguistic particularities of Persian that complicate full alignment with Western testing frameworks such as the CEFR. Despite formal resemblance to international tests like IELTS, SAMFA remains a unique case of language assessment shaped by local norms, educational policy, and ideological imperatives. The findings contribute to the growing field of non-European language proficiency assessment and the challenges of global comparability in high-stakes language testing.